2012
DOI: 10.1007/s10295-011-1048-y
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of rapid enzymatic hydrolysis of crystalline cellulose after pretreatment by NMMO

Abstract: Pretreatment of cellulose with an industrial cellulosic solvent, N-methylmorpholine-N-oxide, showed promising results in increasing the rate of subsequent enzymatic hydrolysis. Cotton linter was used as high crystalline cellulose. After the pretreatment, the cellulose was almost completely hydrolyzed in less than 12 h, using low enzyme loading (15 FPU/g cellulose). The pretreatment significantly decreased the total crystallinity of cellulose from 7.1 to 3.3, and drastically increased the enzyme adsorption capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 36 publications
1
29
0
6
Order By: Relevance
“…In some studies, the experimental setup enabling the continuous elimination of end-products has been used [6]. The numerical values of inhibition constants have been obtained by the fitting of hydrolysis data to the complex equations derived for the full time-course [14-20]. The validity of these figures depends on the validity of the model [21].…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, the experimental setup enabling the continuous elimination of end-products has been used [6]. The numerical values of inhibition constants have been obtained by the fitting of hydrolysis data to the complex equations derived for the full time-course [14-20]. The validity of these figures depends on the validity of the model [21].…”
Section: Introductionmentioning
confidence: 99%
“…Área temática: Processos Biotecnológicosconduzidos à temperatura de 4° C, pois nessa temperatura é possível estudar o fenômeno de adsorção sem a presença da hidrólise da celulose (Kumar e Wyman, 2009;Wang et al, 2011;Khodaverdi et al, 2012;Zheng et al 2013), porém a temperatura é um dos fatores que afeta o processo de adsorção (Site, 2001), assim isotermas de adsorção determinadas em temperaturas diferentes de 50° C não são adequadas para representar a hidrólise enzimática da celulose.…”
Section: Diversos Estudos Com Adsorção De Celulases Em Substatos Celuunclassified
“…Muitos modelos matemáticos de hidrólise enzimática de substratos celulósicos e lignocelulósicos descrevem a etapa de adsorção por meio de isotermas como as de Langmuir e utilizam as mesmas isotermas em todos os momentos da reação (Kadam et al, 2004;Khodaverdi et al, 2012). Esta abordagem assume que as características da adsorção do sistema substrato-enzima não se alteram durante o tempo de hidrólise.…”
Section: A Isoterma De Langmuir é Dada Pela Equação (1)unclassified
“…102 In it, NMMO dissolves cellulose fibers due to its high polarity N-O bond, which breaks the hydrogen bond network of the cellulose and forms new hydrogen bonds with the solute. Recent studies have shown the potential of NMMO for pretreating pure cellulose, 105 sugarcane bagasse, 106 spruce, 107 oak, 107 rice straw, 108 and poplar. 103,104 Since lignin has been shown to be a radial scavenger and antioxidant, lignocellulose can be pretreated in NMMO directly.…”
Section: N-methyl-morpholine-n-oxide (Nmmo)mentioning
confidence: 99%